2001
DOI: 10.1081/jbc-100104146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elf-Emf Treatment on Wheat Seeds at Different Stages of Germination and Possible Mechanisms of Their Origin

Abstract: The efficiency of weak ELF (extremely low frequency) EMF on living systems can be explained by taking into account the nonstationary processes that arise when ions pass part of the intermembrane distance during the EMF period. The periodic movement of ions in the heterogeneous medium would result in the nonlinear effects influencing the ionic strength and pH near the membrane and the release of some peripheral proteins to the water phase. Based on this notion, we studied the effects of EMF treatment (30 or 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Studies carried out by the authors Aksyonov et al (2001) confirmed that the 15 minute treatment of seeds of wheat by the magnetic field of induction of 30 mT caused amplification of root growth by nearly 25%, while the length of the stems of the plants was higher by 40% compared to the control plants. Alexander et Doijode (1995) reports that the use of the magnetic field within the seed treatment before germination improved root growth and viability of rice and onions.…”
Section: Figuresupporting
confidence: 55%
“…Studies carried out by the authors Aksyonov et al (2001) confirmed that the 15 minute treatment of seeds of wheat by the magnetic field of induction of 30 mT caused amplification of root growth by nearly 25%, while the length of the stems of the plants was higher by 40% compared to the control plants. Alexander et Doijode (1995) reports that the use of the magnetic field within the seed treatment before germination improved root growth and viability of rice and onions.…”
Section: Figuresupporting
confidence: 55%
“…Timing is also of great importance from the view point of the timing of application. As Aksyonov et al (2001) demonstrated, the effect of an EMF (30, 50 Hz, 30 mT) was different if it was applied at different stages of germination of wheat seeds. If EMF was applied at the stage of esterase activation, leakage of products from the esterase reaction increased relative to both the untreated and earlier treated seeds.…”
Section: Conclusion and Future Objectivesmentioning
confidence: 93%
“…There was no considerable heating effect of the coils stemming from the current. The highest temperature at the site of the samples located did not exceed 26 8C, which is within the range of temperatures considered optimal for wheat or bean seed germination [Aksyonov et al, 2001]. Current and voltage required to generate MFs was provided by power supplies (Global Dual Power Supply,Model 3521,Wilmington,DE).…”
Section: Exposure Systemmentioning
confidence: 99%